Current perspectives and trends in nanoparticle drug delivery systems in breast cancer: bibliometric analysis and review - Sun, Sheng; Wang, Ye-hui; Gao, Xiang; Wang, He-yong; Zhang, Lu; Wang, Na; Li, Chun-mei; Xiong, Shao-quan (Frontiers in Bioengineering and Biotechnology, 2023)
The treatment of breast cancer (BC) is a serious challenge due to its heterogeneous nature, multidrug resistance (MDR), and limited therapeutic options. Nanoparticle-based drug delivery systems (NDDSs) represent a promising tool for overcoming toxicity and chemotherapy drug resistance in BC treatment. No bibliometric studies have yet been published on the research landscape of NDDS-based treatment of BC. In this review, we extracted data from 1,752 articles on NDDS-based treatment of BC published between 2012 and 2022 from the Web of Science Core Collection (WOSCC) database. VOSviewer, CiteSpace, and some online platforms were used for bibliometric analysis and visualization. Publication trends were initially observed: in terms of geographical distribution, China and the United States had the most papers on this subject. The highest contributing institution was Sichuan University. In terms of authorship and co-cited authorship, the most prolific author was Yu Zhang. Furthermore, Qiang Zhang and co-workers have made tremendous achievements in the field of NDDS-based BC treatment. The article titled “Nanomedicine in cancer therapy: challenges, opportunities, and clinical applications” had the most citations. The Journal of Controlled Release was one of the most active publishers in the field. “Global cancer statistics 2018: GLOBOCAN estimates of incidence and mortality worldwide for 36 cancers in 185 countries” was the most cited reference. We also analysed “hot” and cutting-edge research for NDDSs in BC treatment. There were nine topic clusters: “tumour microenvironment,” “nanoparticles (drug delivery),” “breast cancer/triple-negative breast cancer,” “combination therapy,” “drug release (pathway),” “multidrug resistance,” “recent advance,” “targeted drug delivery”, and “cancer nanomedicine.” We also reviewed the core themes of research. In summary, this article reviewed the application of NDDSs in the treatment of BC.